2007
DOI: 10.1095/biolreprod.107.060947
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Three Vitellogenins by 17beta-Estradiol with Concurrent Inhibition of the Growth Hormone-Insulin-Like Growth Factor 1 Axis in a Euryhaline Teleost, the Tilapia (Oreochromis mossambicus)1

Abstract: The objective of the present study was to utilize the male Mozambique tilapia (Oreochromis mossambicus) as a model for examining the molecular mechanisms that mediate the physiological transition between somatic and gonadal growth in female teleost fish, and in vertebrates in general. Partial cDNAs that encode multiple forms of vitellogenin (Vtg), which is the major precursor of yolk proteins, were cloned from estrogen-treated males and utilized to develop real-time quantitative RT-PCR assays, which were suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 64 publications
9
39
0
3
Order By: Relevance
“…It is well known that the induction of Vtg mRNA expression in fish is achieved by ER activated by E2 (Atteke et al, 2003;Davis et al, 2007). In the present study, E2 also stimulated ERα transcription in concert with the activation of Vtg mRNA expression levels in the liver of male mosquitofish.…”
Section: Effects Of Steroid Hormones On Er Gene Expressionsupporting
confidence: 71%
See 3 more Smart Citations
“…It is well known that the induction of Vtg mRNA expression in fish is achieved by ER activated by E2 (Atteke et al, 2003;Davis et al, 2007). In the present study, E2 also stimulated ERα transcription in concert with the activation of Vtg mRNA expression levels in the liver of male mosquitofish.…”
Section: Effects Of Steroid Hormones On Er Gene Expressionsupporting
confidence: 71%
“…In combined hormone treatments, our present results have some differences compared with a previous study, where both P and T markedly inhibit the induction of hepatic Vtg mRNA in male turtles (Chrysemys picta) by E2, T being the most potent inhibitor (Custodia-Lora et al, 2004). Induction of Vtg gene expression by estrogens is closely related to ER regulation (Atteke et al, 2003;Davis et al, 2007). The present study also confirmed that E2 significantly increase the expression of ERα mRNA in the liver of …”
Section: Effects Of Steroid Hormones On Vtg Gene Expressionsupporting
confidence: 50%
See 2 more Smart Citations
“…O hCG proporciona aumento dos níveis de gonadotrofinas, que estimulam o crescimento folicular e, consequentemente, os níveis de estradiol, que estão relacionados com a incorporação e a vitelogenina nos ovócitos (Davis et al, 2007). Esses ovos são maiores, proporcionando larvas maiores e com saco vitelino maior (Wootton, 1994;Gisbert et al, 2000) e maior sobrevivência larval.…”
Section: Resultsunclassified